Determination Of Freshwater Consumption Fish Diseases Using Artificial Neural Network Methods - Apriyanto, Bagas; Riyadi, Ahmad; Kusuma Wardana, Ari; Nasrun Mohd Nawi, Mohd (APPLIED SCIENCE AND TECHNOLOGY REASERCH JOURNAL, 2024)
Artificial Neural Network (ANN) is a branch of Artificial Intelligence (AI) that uses neuron-based computational methods to identify and solve problems. In this study, we tried to use ANN to identify diseases of freshwater fish commonly consumed by the public, using one of the ANN methods, namely backpropagation. This research produces a website-based system that uses the backpropagation Neural Network method so that it can be used to help freshwater fish breeders or cultivators identify fish diseases that are kept more accurately than conventional methods. In addition, it is hoped that this system can anticipate more severe infections in fish belonging to cultivators. The results of system testing show that regarding the appearance of the system, 38.5% of respondents answered that the design was beautiful, related to the ease of use of the system, 46.2% of respondents answered that the approach was straightforward to use, regarding the performance of the system 53.8% of respondents answered that the system performance was excellent. Regarding the system's benefits, 76.9% of respondents answered that the system was beneficial